PENGARUH MODEL PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) DENGAN MEDIA KARTU MASALAH TERHADAP PEMAHAMAN KONSEP DAN AKTIVITAS BELAJAR SISWA PADA MATERI MOMENTUM DAN IMPULS DI SMA - Cholifatur Rosidah; Sudarti Sudarti; Maryani Maryani (FKIP Universitas Jember, 2018)
AbstractThe type of this research was experimental research with post-test only controlgroup design in SMA Negeri 1 Panji Situbondo 2016/2017. This research purposed toknow the influence of POGIL models with media card problems with understandingstudents and student learning activities. Determination of research sample is usedcluster random sampling, X MIA 4 as experiment class and X MIA 2 as control class.The technique of data analysis were independent sample t-test with program SPSS 22.Based on analysis of Mann-Whitney test result, showed that model of POGIL withmedia card problems have significantly effect to the understanding of the student'sconcept. Based on the analysis of the independent sample t-test results showed thatmodel of POGIL with media card problems have significantly effect to student learningactivities.Keyword: POGIL, understanding the concept, student learning activities